2024
DOI: 10.1021/acs.est.3c06345
|View full text |Cite
|
Sign up to set email alerts
|

Disposable Plastic Waste and Associated Antioxidants and Plasticizers Generated by Online Food Delivery Services in China: National Mass Inventories and Environmental Release

Yu-Qi Huang,
Yuan Zeng,
Jin-Long Mai
et al.

Abstract: China's online food delivery (OFD) services consume enormous amounts of disposable plastics. Here, we investigated and modeled the national mass inventories and environmental release of plastics and chemical additives in the plastic. The extra-tree regression identified six key descriptors in determining OFD sales in Chinese cities. Approximately 847 kt of OFD plastic waste was generated in 2021 (per capita 1.10 kg/yr in the megacities and 0.39 kg/yr in other cities). Various additives were extensively detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The single-use takeaway boxes are becoming a significant source of plastic packaging waste due to their low recyclability . Online food delivery users have reached 2.85 billion worldwide in 2023, whereas the recycling of takeout food boxes is challenging due to the complexities involved in their cleaning process, and thus ∼847 kt of relevant plastic waste was generated annually in China alone . Packaging debris is widespread in rivers, estuaries, and open oceans, and our recent investigation revealed that packaging littering is severe, ranging from 0.33 to 13.5 g·L –1 in the estuarine environment …”
Section: Introductionmentioning
confidence: 99%
“…The single-use takeaway boxes are becoming a significant source of plastic packaging waste due to their low recyclability . Online food delivery users have reached 2.85 billion worldwide in 2023, whereas the recycling of takeout food boxes is challenging due to the complexities involved in their cleaning process, and thus ∼847 kt of relevant plastic waste was generated annually in China alone . Packaging debris is widespread in rivers, estuaries, and open oceans, and our recent investigation revealed that packaging littering is severe, ranging from 0.33 to 13.5 g·L –1 in the estuarine environment …”
Section: Introductionmentioning
confidence: 99%